2015
DOI: 10.1177/2047487315613462
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of mobile-health behaviour change interventions for cardiovascular disease self-management: A systematic review

Abstract: Our review found mHealth has the potential to change lifestyle behaviour. Results are still limited to a small number of trials, inconsistent outcome measures and ineffective reporting of intervention characteristics. Large scale, longitudinal studies are now warranted to gain a clear understanding of the effects of mHealth on behaviour change in the cardiovascular disease population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(114 citation statements)
references
References 44 publications
4
108
1
1
Order By: Relevance
“…Motivating factors included their experience of benefits from physical activity, the ability to use physical activity as a mental distraction and the desire to use physical activity as a means to maintain "normality" in life. These findings are generally consistent with prior work in lung cancer and palliative care populations reporting the majority of patients are interested in and feel able to participate in exercise programmes (Lowe, Watanabe, Baracos, & Courneya, 2010) and a desire for more support (Smith et al, 2017 (Pfaeffli, Dobson, Whittaker, & Maddison, 2016).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Motivating factors included their experience of benefits from physical activity, the ability to use physical activity as a mental distraction and the desire to use physical activity as a means to maintain "normality" in life. These findings are generally consistent with prior work in lung cancer and palliative care populations reporting the majority of patients are interested in and feel able to participate in exercise programmes (Lowe, Watanabe, Baracos, & Courneya, 2010) and a desire for more support (Smith et al, 2017 (Pfaeffli, Dobson, Whittaker, & Maddison, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…Behavioural change interventions are effective in a variety of chronic health conditions to increase physical activity levels (Avery et al, ; O'halloran et al, ), including populations with breast cancer (Bluethmann, Vernon, Gabriel, Murphy, & Bartholomew, ). A recent systematic review in cardiovascular disease demonstrated that mobile wireless devices used to deliver self‐management interventions successfully improved physical activity levels (Pfaeffli, Dobson, Whittaker, & Maddison, ). Changing behaviour is not an easy task and many cancer trials delivering physical activity interventions achieve improvements in a variety of outcomes including fitness, but not in physical activity behaviour (Bourke et al, ; Hudis & Jones, ).…”
Section: Discussionmentioning
confidence: 99%
“…Telehealth interventions are cost‐effective, fast and useful, and provide effective solutions; they have an important role in maintaining regular and continuous communication with the patient, and can be used in monitoring, training and consulting the patient . There have been many randomised controlled trials (RCTs) with telehealth interventions to reduce risk factors and improve adherence to lifestyle changes such as medication, physical activity, smoking cessation, blood pressure, lipids, physical activity and waist circumference; in physical activity , medication adherence , smoking cessation , lipid changes and risk factor modification . Results from these studies support the beneficial effect of telehealth interventions within CAD management programs on adherence to lifestyle changes.…”
Section: Introductionmentioning
confidence: 86%
“…A limitation of the studies to date in this regard is that most have focused on improving physical activity [53]. Further, a Cochrane review of this literature found the studies to be too heterogeneous in approach to draw definitive conclusions regarding their efficacy [54].…”
Section: Health Team and System-related Factorsmentioning
confidence: 99%